The IMPLEMENTATION OF PROBLEM BASED LEARNING METHOD IN TEACHING WRITING PROCEDURE TEXT ON NINTH GRADE AT MTsN 01 BINJAI - Dini Fakhira Dini (Journal of Education, Linguistics, Literature and Language Teaching, 2024)
The purpose of this research was to know the implementation of PBL method and to know the affect of PBL method on the students' ability in writing procedure text on ninth grade at MTsN 01 Binjai. This research used a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest design. The population in this research was all ninth grade consisting of ten classes. The sample for this research was class IX-7 which consisted of 22 students and was selected using by purposive sampling technique. This research used a writing test in the form of procedure text in collecting data and research instruments. This research carried out three treatment meetings. Data were analyzed using the T-test. The results of this research indicated that the implementation of the Problem Based Learning (PBL) method was carried out according to the five existing stages, where each stage in the writing learning process has outcomes at each step and contributed to the achievement of effective learning to improve students' writing ability. Another result showed that there was increased in students' writing abilities. This is proven by the significant increased between students' pretest and post-test scores. The average student score increased from 52.72% (pre-test) to 83.63% (post-test) and statistical results using the t-test between pre-test and post-test were 30.91% (680). This means that students' writing results improved after implementing the PBL method. The PBL method is also a learning method that is able to have a positive effect on students' writing skills in procedure text.